Manajemen Risiko Pada UMKM “Toko Bangunan Kulsum di Pangalengan, Jawa Barat” - Siti Kulsum, Reysa; Riskiawati, Suci; Lestari3, Trie Ayu (Universitas Serambi Mekkah, 2024)
This study evaluates various risk management aspects in a building material store using a SWOT approach to identify risks and mitigation strategies. Risks are categorized into operational, human resources, financial, market, marketing, and legal domains. Strengths stem from the founder's experience and supplier network, while weaknesses are associated with manual record-keeping and limited technological adoption. To minimize potential risks and enhance resource efficiency, it is recommended to develop the existing systems and improve recruitment processes.